Sorption of arsenate and arsenate anions by iron(III)-poly(hydroxamic acid) complex - Haron, M.J.; Wan Yunus, W.M.Z.; Yong, N.L.; Tokunaga, S. (Elsevier, 1999)
Iron(III)-poly(hydroxamic acid) resin complex has been studied for its sorption abilities with respect to arsenate and arsenite anions from an aqueous solution. The complex was found effective in removing the arsenate anion in the pH range of 2.0 to 5.5. The maximum sorption capacity was found to be 1.15 mmol/g. The sorption selectivity showed that arsenate sorption was not affected by chloride, nitrate and sulphate. The resin was tested and found effective for removal of arsenic ions from industrial wastewater samples.